2005
DOI: 10.1158/1535-7163.mct-05-0216
|View full text |Cite
|
Sign up to set email alerts
|

Antimitogenic and chemosensitizing effects of the methylation inhibitor zebularine in ovarian cancer

Abstract: Deoxycytosine methylation within CpG islands of tumor suppressor genes plays a prominent role in the development and progression of drug-resistant ovarian cancer. Consequently, epigenetic therapies directed toward tumor suppressor demethylation/reexpression could potentially reverse malignant phenotypes and chemosensitize recalcitrant tumors. In this report, we examined the demethylating agent zebularine [1-(B-D-ribofuranosyl)-1,2-dihydropyrimidin-2-one], in comparison with the well-known methylation inhibitor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 54 publications
2
103
0
2
Order By: Relevance
“…Previous studies showed that the fragile WWOX gene is inactivated in a significant fraction of breast cancers (8,9), mainly due to DNA hypermethylation (13). DNA hypermethylation can be reversed by DNA methyltransferase inhibitors, such as DAC (24) or zebularine (25), agents that have therapeutic potential for cancers. Thus, we determined if restoration of Wwox expression in breast cancer cells lacking expression of endogenous Wwox would reverse cancer cell growth despite the numerous genetic alterations that have accumulated in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the fragile WWOX gene is inactivated in a significant fraction of breast cancers (8,9), mainly due to DNA hypermethylation (13). DNA hypermethylation can be reversed by DNA methyltransferase inhibitors, such as DAC (24) or zebularine (25), agents that have therapeutic potential for cancers. Thus, we determined if restoration of Wwox expression in breast cancer cells lacking expression of endogenous Wwox would reverse cancer cell growth despite the numerous genetic alterations that have accumulated in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to dZTP leads to reexpression of the cell cycle and apoptosis modulator RASSF1A after demethylation of its promoter in ovarian cancer cells and in a lymphoma mouse model. [62][63][64] However, higher doses of dZTP are required to obtain demethylation and gene reexpression levels comparable to those induced by azanucleosides. This may be because of its lower binding affinity for uridine/cytidine kinase, the enzyme responsible for nucleoside analog activation, or its sequestration by cytidine deaminase.…”
Section: Other Nucleoside Inhibitorsmentioning
confidence: 99%
“…Although this drug works in a manner similar to 5-Aza-CR and 5-Aza-CdR, it is more stable and less toxic than 5-Aza-CR and 5-Aza-CdR DNMTis (Zhou et al, 2002;Cheng et al, 2003). In line with these findings, zebularine has been shown to reactivate tumor suppressor genes (Flotho et al, 2009;Billam et al, 2010), enhance tumor cells' chemotherapy and radiation sensitivity (Dote et al, 2005), exert angiostatic and antimitogenic activities (Balch et al, 2005;Hellebrekers et al, 2006) and to be stable enough for oral administration (Zhou et al, 2002;Cheng et al, 2003). In addition, at low doses, zebularine can be given to patients continuously without the overt cytoxicity associated with 5-Aza-CR and 5-Aza-CdR.…”
Section: Dna Methyltransferase Inhibitors (Dnmtis)mentioning
confidence: 76%